Seepage and stability analysis of fractured soil slope considering permeability anisotropy - Chunli Zhang; Mengdi Qin; Long Hong; Yunfei Qi (Scientific Reports)
Abstract Slope fractures play an important role in slope destabilization accidents induced by rainfall, but its influence on seepage field and slope stability is not fully studied, especially under the conditions of soil permeability anisotropy. This study aims to investigate the influence of anisotropic permeability property of soil and fractures on the seepage field and slope stability under rainfall conditions. The surface cracks of the slope are regarded as continuous medium, and the saturated-unsaturated seepage theory is applied to the numerical simulation of the fractured soil slopes with different anisotropic permeability ratios by Geo-studio software. The evolution of seepage field and slope stability under the rainfall conditions are investigated using finite element simulation tool. The simulation results reveal that fractures mainly impact the pressure distribution in the seepage field of the shallow layer of slope, and have little effect on the deep layer. Furthermore, the anisotropic permeability of the soil has a significant effect on the seepage field, safety factor, and fracture action of the slope under rainfall conditions. These findings provide critical insights into slope engineering and management under anisotropic soil conditions.